Trade and Investment Relations Between Uzbekistan and the European Union : Challenges and Opportunities. - Abdullaeva, Samira; Bolotov, Ilya; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis provides a comprehensive examination of the evolution and present state of the trade/investment relationship between Uzbekistan and the European Union (EU). The research will employ a comparative analysis using data obtained from the European Commission, UNCTAD, the World Bank, and the IMF, to explore the trends in bilateral trade between Uzbekistan and the EU, the types of exports from Uzbekistan, the investment activity in Uzbekistan by EU member countries (Direct Foreign Investment), and the interaction of Uzbekistan with EU member countries. In examining the evolutionary and present state of this trade/investment relationship, the research incorporates the Dependency Theory and Resource Curse perspective, as well as the use of Comparative Geopolitical Perspectives to understand the findings produced by the empirical evidence. Findings of the research show a structural asymmetry between Uzbekistan's exports to the EU (primarily raw material goods) and EU imports from Uzbekistan (mostly high-value manufactured goods). In comparison to other countries (i.e., Russia and China), the EU has followed a normative/sustainability-oriented approach towards investment activities in Uzbekistan. Therefore, it is critical for Uzbekistan to address its significant limitations regarding institutional structure and modernisation to reduce dependency on the EU's commodity export model.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses